2018
DOI: 10.1159/000486764
|View full text |Cite
|
Sign up to set email alerts
|

Immune Gene Expression Profile in Hepatocellular Carcinoma and Surrounding Tissue Predicts Time to Tumor Recurrence

Abstract: Background: The antitumor immune response may play a major role in the clinical outcome of hepatocellular carcinoma (HCC). We characterized the liver immune microenvironment by direct hybridization of RNA extracted from HCC and nontumorous tissues. Methods: RNA was extracted from frozen liver tissue samples of HCC (T; n = 30) and nontumorous tissues (NT; n = 33) obtained from 38 patients. Matched samples were available for 25 patients. The immune gene expression profile was analyzed with the nCounter GX Human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
5
16
1
Order By: Relevance
“…In our study, based on selective analysis of immune response-related transcripts, we identified a subset of non-tumorous tissues characterized by globally increased immune gene expression, where all cell types, including both activated and exhausted phenotypes, were predicted to be more represented. 116 This immune gene profile was associated with shorter TTR, consistent with our earlier observations 42…”
Section: Global Appraisal Of the Immune Landscape: Immune Signaturessupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, based on selective analysis of immune response-related transcripts, we identified a subset of non-tumorous tissues characterized by globally increased immune gene expression, where all cell types, including both activated and exhausted phenotypes, were predicted to be more represented. 116 This immune gene profile was associated with shorter TTR, consistent with our earlier observations 42…”
Section: Global Appraisal Of the Immune Landscape: Immune Signaturessupporting
confidence: 89%
“…118 Most cell types of lymphoid and myeloid lineages were more represented in tumours with longer TTR, with special enrichment of cytotoxic cells. 116 Only Treg and Th17 subsets were predicted to be more frequent in tumours with worse prognosis, as described previously. 57,118 In a recent report, RNA sequencing data indicated that an immune landscape rich in T cells and cytotoxic cells, but lacking macrophages and Th2 cells, was positively correlated with patient survival.…”
Section: Global Appraisal Of the Immune Landscape: Immune Signaturessupporting
confidence: 62%
See 2 more Smart Citations
“…In addition, immune cell infiltration is associated with the clinical outcome of hepatic cancer [20]. …”
Section: Keynote-224 Trialmentioning
confidence: 99%